Contemplating Media Globalisation on World’s Issues: A Case of Malaysian Responses to the Tufan al-Aqsa’s Gaza Crisis - Chun-Leung, Jacky Li; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2025)
This paper aims to discuss how the role of media globalisation shapes Malaysian consumers to show their Muslim identity while the international class of regional crisis happens or even reaches Malaysia. One of the events which have always been in the radar is the conflict between Israel and Palestine. It has been a focus worldwide on Gaza after the Tufan al-Aqsa started on 7 October 2023. The media has exposed the issue from different perspectives, including those who support or accuse Hamas in this recent conflict. However, Hamas is still being labelled as a terror organisation by the West. This article will choose McDonald’s and HP as examples to discuss why the boycott campaign against McDonald’s but not HP products, gain support from the people soon after the outbreak of the Gaza conflict in 2023. This is especially how media globalisation accelerated the fast-growing boycott campaign in Malaysia.